The Implementation of Rough Set on A Group Structure - Ananto Adi Nugraha; Fitriani Fitriani; Muslim Ansori; Ahmad Faisol (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2022)
Let be a non-empty set and an equivalence relation on . Then, is called an approximation space. The equivalence relation on forms disjoint equivalence classes. If , then we can form a lower approximation and an upper approximation of . If X⊆U, then we can form a lower approximation and an upper approximation of X. In this research, rough group and rough subgroups are constructed in the approximation space for commutative and non-commutative binary operations.